2020
DOI: 10.1177/0016986220941587
|View full text |Cite
|
Sign up to set email alerts
|

Test-Taking for Gifted and Talented Kindergarten: Underscoring the Importance of Outreach

Abstract: Using proprietary data collected prior to the establishment of the public Universal Prekindergarten program in New York City, this study finds statistically significant differences in test-taking rates for the city’s Gifted & Talented (G & T) program between two matched samples of students—those who attended a public prekindergarten (pre-K) program and those who did not—for each of four cohorts from 2008 to 2011, favoring the public pre-K group. Results also demonstrate that access to information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…The results of these efforts indicate that researchbased practices, including access to information, work to improve the participation of diverse student populations in gifted programming. Lu et al (2020) used New York City's Department of Education data to examine the relationship between test-taking gaps for participation in gifted and talented (GT) programs and access to information regarding GT programs among public school and nonpublic school kindergarteners from 2008 to 2011. The authors found that the public school cohort had greater access to information and higher rates of GT test-taking than the nonpublic school cohort.…”
Section: Accessing Information Via Websitesmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of these efforts indicate that researchbased practices, including access to information, work to improve the participation of diverse student populations in gifted programming. Lu et al (2020) used New York City's Department of Education data to examine the relationship between test-taking gaps for participation in gifted and talented (GT) programs and access to information regarding GT programs among public school and nonpublic school kindergarteners from 2008 to 2011. The authors found that the public school cohort had greater access to information and higher rates of GT test-taking than the nonpublic school cohort.…”
Section: Accessing Information Via Websitesmentioning
confidence: 99%
“…In our study, we examine the accessibility and availability of information on district websites. Research has shown that when parents are made aware of gifted education programming within school districts, gaps in equity close (Lu et al, 2020; Olszewski-Kubilius et al, 2004). Understanding the accessibility and availability of information can help frame a possible cause for gaps in equity.…”
Section: Purposementioning
confidence: 99%
See 3 more Smart Citations